AN APPLICATION OF DISCONTINUOUS GALERKIN METHOD FOR BLAST WAVE SIMULATIONS - (:unkn) unknown (AMER SOC MECHANICAL ENGINEERS, 2010)
An implementation of Runge-Kutta Discontinuous Galerkin method to an in-house computational fluid dynamics code capable of simulating blast waves was performed. The resultant code was tested for two shock tube problems with moderately and extremely strong discontinuities. Numerical solutions were compared with predictions of a finite volume method and exact solutions. It was observed that when there are extreme discontinuities in the flowfield, as in the case of blast waves, the limiter adopted for solution clearly affects the overall quality of the predictions. An alternative limiting technique was proposed and tested to improve the results obtained. Blast wave predictions using Runge-Kutta Discontinuous Galerkin method with the alternative limiting technique yielded slightly stronger and faster moving shock waves compared to finite volume solutions.
Keywords: FINITE-ELEMENT-METHOD; CONSERVATION-LAWS; SCHEMES; SYSTEMS